2011
DOI: 10.3390/rs3122605
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Accounting for Atmospheric Effects in the Application of NDVI and Interpretation of Satellite Imagery Supporting Archaeological Research: The Case Studies of Palaepaphos and Nea Paphos Sites in Cyprus

Abstract: This paper presents the findings of the impact of atmospheric effects when applied on satellite images intended for supporting archaeological research. The study used eleven multispectral Landsat TM/ETM+ images from 2009 until 2010, acquired over archaeological and agricultural areas. The modified Darkest Pixel (DP) atmospheric correction algorithm was applied, as it is considered one of the most simple and effective atmospheric corrections algorithm. The NDVI equation was applied and its values were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 37 publications
0
37
0
2
Order By: Relevance
“…From examples carried out from the authors (not shown here) it was found that without atmospheric correction, OOMW index can give even negative values in pixels with OOMW disposal areas. Image-based atmospheric corrections algorithms, as those of the DP method, can be easily applied by users and solved this problem [Agapiou et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…From examples carried out from the authors (not shown here) it was found that without atmospheric correction, OOMW index can give even negative values in pixels with OOMW disposal areas. Image-based atmospheric corrections algorithms, as those of the DP method, can be easily applied by users and solved this problem [Agapiou et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…the effects of the atmosphere must be taken into account (Hadjimitsis et al 2010 andAgapiou et al 2011). Ratio form of NDVI makes it susceptible to variations in atmospheric conditions, surface conditions, topography, and sensor characteristics, none of which has any relationship with vegetation (Gitelson 2004 andRahetlah et al 2014).…”
Section: Discussionmentioning
confidence: 98%
“…In this example (see Agapiou et al 2011b) an archive series of Landsat dataset is being used over the archaeological sites of "Nea Paphos" and "Palaepaphos" in Cyprus ( …”
Section: Atmospheric Correction Of Archive Satellite Datamentioning
confidence: 99%